Meta-analysis of the effects of Lactobacillus plantarum and Lactobacillus buchneri on fermentation, chemical composition and aerobic stability of sugarcane silage - Silveira Rabelo, Carlos Henrique [UNESP]; Harter, Carla Joice [UNESP]; Silva Avila, Carla Luiza da; Reis, Ricardo Andrade [UNESP] (Wiley-Blackwell, 2019)
We conducted a meta-analysis to investigate the impact of Lactobacillus plantarum or Lactobacillus buchneri on the fermentation, chemical composition, and aerobic stability of sugarcane silage. Two databases that included 15 and 27 published articles (81 and 83 silages evaluated) were used to evaluate L. plantarum and L. buchneri, respectively. For each database, the means of the treatments compiled from the studies were classified into two categories: (a) sugarcane silage without inoculant (untreated) and (b) sugarcane silage inoculated with L. plantarum (1 x 10(5)-1.8 x 10(6) cfu/g of fresh forage) or with L. buchneri (2.5 x 10(4)-1 x 10(6) cfu/g of fresh forage; inoculated). Sugarcane silage inoculated with L. plantarum displayed increased ethanol concentration (+43.8%, p < 0.01) and dry matter (DM) loss (+9.6%, p = 0.03). In contrast, inoculation with L. buchneri increased the acetic acid concentration (+30.8%, p = 0.01), and decreased ethanol concentration (-58.8%, p < 0.01) and DM loss (-19.7%, p < 0.01). In vitro DM digestibility decreased following inoculation with L. plantarum (-5.7%, p = 0.05) or L. buchneri (-3.3%, p < 0.01). Aerobic stability was unaffected by inoculation with L. plantarum (p = 0.16) or L. buchneri (p = 0.48). The results show that L. plantarum impairs the fermentation of sugarcane silages; therefore, its utilization might not be recommended for ensiling this crop. Conversely, even with no additional gain on silage digestibility and aerobic stability, L. buchneri may be recommended for sugarcane ensiling because it reduces alcoholic fermentation and DM loss.
Keywords: dry matter loss; ethanol; Lactobacillus buchneri; Lactobacillus plantarum; sugarcane